2019
DOI: 10.1111/ceo.13579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of VEGF inhibitors on human retinal pigment epithelium under high glucose and hypoxia

Abstract: Background Retinal pigment epithelium (RPE) is known to secrete factors important for retinal homeostasis. How this secretome changes in diabetic eyes treated with anti‐vascular endothelial growth factor (VEGF) inhibitors is unclear. Methods Diabetic conditions were simulated in vitro using ARPE‐19 cell‐line culture, with high glucose (25 mM) culture media, and hypoxia was chemically induced using cobalt chloride. Stress was assessed using cell viability assays as well as Western blots and enzyme‐linked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…We could not see a significant increase in HIF-2α expression under a CoCl 2 -induced hypoxic condition, and rice bran and vitamin B6 did not change its expression. Taken together, it indicates that HIF-1α (rather than HIF-2α) might be the major regulator in ARPE-19 cells under this hypoxic condition, which is in agreement with several previous reports using ARPE-19 cells [33][34][35].…”
Section: Rice Bran or Vitamin B6 Inhibits The Hif/vegf Axis In Arpe-1supporting
confidence: 93%
“…We could not see a significant increase in HIF-2α expression under a CoCl 2 -induced hypoxic condition, and rice bran and vitamin B6 did not change its expression. Taken together, it indicates that HIF-1α (rather than HIF-2α) might be the major regulator in ARPE-19 cells under this hypoxic condition, which is in agreement with several previous reports using ARPE-19 cells [33][34][35].…”
Section: Rice Bran or Vitamin B6 Inhibits The Hif/vegf Axis In Arpe-1supporting
confidence: 93%
“…The duration of hypoxia and glucose concentrations in vitro systems should be of practical relevance to the brain in vivo. However, the duration of hypoxia and glucose concentrations to induce hypoxia and hyperglycemia was varied in different in vitro models [20,21,27]. Our data showed that cells exposed to high glucose (33 mM) 24 h prior to a 24 h anaerobic incubation (3% O 2 ) resulted in moderate microglial cell death as compared with hypoxia (3% O 2 ) alone for 24 h.…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies found that methyltransferase-like 3 (METTL3) mediated m 6 A modifications were closely related with the development of type 2 diabetes mellitus (T2DM) [6], but it was still unclear whether METTL3 regulated DR progression. The high-glucose treated retinal pigment epithelium (RPE) cells were used in this study as the in vitro models for DR research according to the previous studies [36][37][38]. The results showed that METTL3 was low expressed in the peripheral venous blood samples collected from T2DM patients compared to the normal volunteers.…”
Section: Figure 4 High-glucose Inhibited Rpe Cell Viability By Regulmentioning
confidence: 99%